Impact of MGNREGS on Labour Supply to Agricultural Sector of Wayanad District in Kerala - Merin S. Thadathil and Vineeth Mohandas (Agricultural Economics Research Review, 2012)
The study has explored the impact of MGNREGS on the labour supply in the agricultural sector of the agrarian district Wayanad in Kerala. The study conducted using primary and secondary data has found that MGNREGS did have an impact on the agricultural sector at the time of its introduction, and does have a role in the hike in the labour wages. The MGNREGS wage acts as a standard minimum wage, keeping the labour market wage high. But, it is not really responsible for the movement of labour from the agricultural sector today. The scheme has been found effective in rural poverty alleviation and women empowerment. It was also found that Neighbourhood help Groups (NHGs) like Kudumbasree have played a major role in the success of MGNREGS in the Wayanad district. The study has outlined some suggestions also for the effective implementation of the MGNREGS.